1984
DOI: 10.2527/jas1984.582356x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Dietary Calcium, Phosphorus and Copper on Performance and Liver Stores of Pigs

Abstract: Three experiments involving 304 pigs were conducted to determine the related effects of copper (Cu), calcium (Ca) and phosphorus (P) on the performance and liver Cu stores of growing-finishing pigs. Rate and efficiency of gain were improved by the addition of 250 ppm of Cu to the diets. Improvements in rate of gain averaged 6.6% (652 vs 696 g/d) to 60.5 kg body weight and 1.7% (713 vs 725 g/d) to 94.5 kg body weight. Feed:gain ratio was improved by 1.4% to 60.5 kg and 1.6% to 94.5 kg body weight when Cu was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…The growth rate response to high levels of dietary Cu in the form of CuSO 4 is well documented in the literature (Bunch et al, 1961(Bunch et al, , 1963Braude, 1967Braude, , 1975Wallace, 1967;Kline et al, 1971Kline et al, , 1973Cromwell et al, 1978;Prince et al, 1979Prince et al, , 1984Stahly et al, 1980;de Lima et al, 1981;Roof and Mahan, 1982;Edmonds et al, 1985;Hagen et al, 1987;Burnell et al, 1988). In our current study, the dietary inclusion of 250 ppm level of Cu (as CuSO4) improved growth rate 24 to 39% and improved efficiency of feed utilization 11 to 21%.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The growth rate response to high levels of dietary Cu in the form of CuSO 4 is well documented in the literature (Bunch et al, 1961(Bunch et al, , 1963Braude, 1967Braude, , 1975Wallace, 1967;Kline et al, 1971Kline et al, , 1973Cromwell et al, 1978;Prince et al, 1979Prince et al, , 1984Stahly et al, 1980;de Lima et al, 1981;Roof and Mahan, 1982;Edmonds et al, 1985;Hagen et al, 1987;Burnell et al, 1988). In our current study, the dietary inclusion of 250 ppm level of Cu (as CuSO4) improved growth rate 24 to 39% and improved efficiency of feed utilization 11 to 21%.…”
Section: Discussionsupporting
confidence: 76%
“…The magnitude of the improvement in growth rate and feed:gain ratio was diminished when Cu (as CuSO4) was increased to 375 ppm and was completely lost when the diet was increased to 500 ppm Cu. Longer-term studies with growing-finishing pigs have shown that the feeding of 500 ppm Cu as CuSO4 depressed performance in pigs (Kline et al, 1971(Kline et al, , 1973Prince et al, 1984), and in certain instances, toxicities have been reported (Wallace et al, 1960;NRC, 1980). However, our results indicate that with young pigs fed for a 4-to 5-wk period, 500 ppm Cu does not depress growth rate compared with pigs fed a low-Cu control diet, although it did reduce efficiency of feed utilization in some instances (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding heifers 0.39% P also increased (P < 0.01) bone Cu content compared with feeding heifers 0.29% P. Bovine bone contains approximately 10 μg of copper per g (Doyle, 1979) on an ash basis and copper plays an important role in collagen maturation linked to its function as a cofactor in lysyl oxidase (Turnlund, 2006). Increasing dietary P from nonphytin sources can adversely affect Cu bioavailability by increasing Cu excretion (Rama Rao et al, 2003), but that does not explain lower bone Cu content observed in this study when heifers were fed diets containing 0.29% P compared with feeding heifers 0.39% P. Prince et al (1984) reported increased levels of liver Cu when pigs were fed high levels of dietary P (>1.00) but could not discount potential Cu contamination in P supplements used to alter dietary P. Likewise, in this study the need for intensive measurement of dietary Cu was not foreseen and thus not undertaken; therefore, dietary influences in regard to differences in bone Cu content observed in this study cannot be dismissed.…”
Section: Discussionmentioning
confidence: 59%
“…The total Ca:P ratio in feeds containing soybean bran can vary from 1:1 to 1.25:1 (NRC, 1998). The ratio can be less critical if excess phosphorus occurs (Prince et al, 1984, Hall et al, 1991. However, excess calcium in the diets reduces organic phosphorus bioavailability (Jongbloed et al, 1993).…”
Section: Resultsmentioning
confidence: 99%